The Implementation of Learning Models Team Game Tournament (TGT) In Increasing Student Activeness in the History of Islamic Culture Subject - Amrulloh, Lutfi; Irhamudin, Irhamudin; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to implement a learning model Team Game Tournament (TGT) in increasing student activity in the History of Islamic Culture subject in class X MA Ma'arif 14 Bumi Nabung. The TGT model was chosen because it was considered capable of creating a more interactive and enjoyable learning atmosphere, so that it could encourage students' active participation in the teaching and learning process. Problems that often arise in teaching and learning activities (KBM), especially in learning the History of Islamic Culture (SKI) in class This research uses a qualitative approach with descriptive methods. Data was collected through observation, interviews and documentation, with research samples from class X MA Ma'arif 14 and Islamic Cultural History subject teachers. This research used triangulation of sources and techniques to ensure the authenticity of the data. The research results show that the implementation of the TGT model has succeeded in increasing student activity in learning, as seen from increased student participation in discussions, group work and academic competitions. Apart from that, students also show higher enthusiasm and motivation in studying the History of Islamic Culture material. Thus, it can be concluded that the TGT learning model is effective in increasing student activity and can be used as an innovative alternative learning model at MA Ma'arif 14 Bumi Nabung